toner

By using the binder of crystalline and non-crystalline resins and calcium carbonate particles in the toner to form a matrix domain structure, the low-temperature curing and scratch-resistant properties of the toner during high-speed printing are solved, and the effect of efficient curing and wear resistance is achieved.

JP7654477B2Active Publication Date: 2025-04-01CANON KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021098009
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-11
Publication Date
2025-04-01
Estimated Expiration
2041-06-11

AI Technical Summary

Technical Problem

In the high-speed printing, especially when printing paper containing a large number of inorganic fine particles, such as cardboard coated paper, it is difficult to achieve low temperature curing and wear resistance to external forces such as friction and scratches simultaneously.

Method used

A binding agent composed of the first crystalline resin and the second amorphous resin is used in combination with calcium carbonate particles, and a matrix domain structure is formed by adjusting the content and distribution of the particles to improve the low-temperature curing and wear resistance of the toner.

Benefits of technology

While efficient curing under low temperature conditions, it improves the adhesion and scratch resistance of the toner to inorganic fine particles in the paper, ensuring the stability and durability of the printed image.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654477000001
    Figure 0007654477000001
  • Figure 0007654477000002
    Figure 0007654477000002
  • Figure 0007654477000003
    Figure 0007654477000003
Patent Text Reader

Abstract

To provide a toner that can achieve both low temperature fixability and scratch resistance.SOLUTION: A toner has a toner particle that contains a binder resin having a first resin and a second resin and calcium carbonate particles. The first resin is a crystalline resin, and the second resin is an amorphous resin. The content of the calcium carbonate particles in the toner particle is 1 mass% or more and 15 mass% or less. A monomer unit constituting the second resin has any one of a nitrile group, a carboxy group, and a hydroxy group, and the total functional group concentration of the groups is 0.8 mmol / g or more and 10.0 mmol / g or less. In a cross section of the toner particle observed by a transmission electron microscope, a matrix-domain structure is present which is composed of a matrix including the first resin and domains including the second resin. The ratio of the matrix including the first resin occupied in the total area of the cross section of the toner particle is 35 area% or more and 70 area% or less. The calcium carbonate particles are contained in an area within 100 nm from the contour of the cross section of the toner particle.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a toner used in an electrophotographic system, an electrostatic recording system, an electrostatic printing system, a toner jet system, and the like. [Background technology]

[0002] In recent years, as full-color electrophotographic copiers have become more widespread, there has been an ever-increasing demand for faster printing and energy conservation. To accommodate high-speed printing, technology that melts toner more quickly in the fixing process is being considered. Also, to improve productivity, technology that shortens the time for various controls during a job and between jobs is being considered. Also, as an energy-saving measure, technology that fixes toner at a lower temperature is being considered in order to reduce power consumption in the fixing process. Furthermore, there is a demand for compatibility with various media such as thick paper and coated paper. Coated paper is often treated as high-quality paper in terms of its glossy feel, and a high level of image quality is also required. On the other hand, it is known that a toner having a binder resin mainly composed of a crystalline resin having sharp melting properties has excellent low-temperature fixing properties compared to a toner having an amorphous resin as the main component. For example, Patent Document 1 describes a toner having a matrix domain structure (sea-island structure) having a matrix containing a crystalline resin having a predetermined melting point range and a domain containing an amorphous resin. This allows for fixing with low energy and provides a toner that can obtain an image that is resistant to external forces such as rubbing and scratching. Patent Document 2 describes a toner that contains a binder resin containing a crystalline resin and an amorphous resin, calcium carbonate particles, and a specific crystalline composite resin as the crystalline resin, thereby obtaining a toner with excellent low-temperature fixing property and transferability. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-142632 A [Patent Document 2] JP 2016-114828 A Summary of the Invention [Problem to be solved by the invention]

[0004] The toner described in Patent Document 1 has a matrix domain structure, and has excellent fixing properties at low energy because a crystalline resin having sharp melting properties forms the matrix. The toner described in Patent Document 2 is said to have excellent low-temperature fixing properties and transferability due to a combination of a binder resin containing a specific crystalline resin and an amorphous resin with calcium carbonate particles. However, when thick coated paper is used under high speed printing, there is room for improvement in terms of obtaining images that are resistant to external forces such as rubbing and scratching, in addition to low temperature fixability. The present invention provides a toner that exhibits excellent low-temperature fixing property and also exhibits excellent abrasion resistance even in images fixed onto media containing a large amount of inorganic fine particles, such as thick coated paper. [Means for solving the problem]

[0005] The present invention provides a toner having toner particles containing a binder resin having a first resin and a second resin, and calcium carbonate particles, the first resin is a crystalline resin and the second resin is an amorphous resin; the content of the calcium carbonate particles in the toner particles is 1% by mass or more and 15% by mass or less, the monomer unit constituting the second resin has any one of a nitrile group, a carboxy group, and a hydroxy group, and the total functional group concentration of these groups is 0.8 mmol / g or more and 10.0 mmol / g or less; a matrix domain structure constituted by a matrix containing the first resin and a domain containing the second resin is present in a cross section of the toner particle observed by a transmission electron microscope, a ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle is 35 area % or more and 70 area % or less; The toner is characterized in that the calcium carbonate particles are contained in an area 100 nm inside from the contour of the cross section of the toner particle. Effect of the Invention

[0006] According to the present invention, it is possible to provide a toner having excellent low-temperature fixing properties and excellent abrasion resistance in fixed images formed on thick coated paper or the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including the lower and upper limits which are the endpoints, unless otherwise specified. (Meth)acrylic acid ester means acrylic acid ester and / or methacrylic acid ester. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. "Monomer unit" refers to the reacted form of a monomer substance in a polymer. For example, one section of a carbon-carbon bond in the main chain in which a vinyl monomer in a polymer is polymerized is considered to be one unit. A vinyl monomer can be represented by the following formula (Z).

[0008] [ka] In formula (Z), R Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group), R Z2 represents an optional substituent. The crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.

[0009] The present invention provides a toner having toner particles containing a binder resin having a first resin and a second resin, and calcium carbonate particles, the first resin is a crystalline resin and the second resin is an amorphous resin; the content of the calcium carbonate particles in the toner particles is 1% by mass or more and 15% by mass or less, the monomer unit constituting the second resin has any one of a nitrile group, a carboxy group, and a hydroxy group, and the total functional group concentration of these groups is 0.8 mmol / g or more and 10.0 mmol / g or less; a matrix domain structure constituted by a matrix containing the first resin and a domain containing the second resin is present in a cross section of the toner particle observed by a transmission electron microscope, a ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle is 35 area % or more and 70 area % or less; The calcium carbonate particles are characterized in that they are contained in an area 100 nm inside from the contour of the cross section of the toner particle.

[0010] As a result of extensive research, the inventors have found that the above-mentioned problem can be solved by incorporating a predetermined amount of calcium carbonate particles into toner particles, forming a matrix domain structure consisting of a matrix containing a first resin, which is a crystalline resin, and a domain containing a second resin, which is an amorphous resin, and by controlling the area occupied by the first resin in the cross section of the toner particle and by incorporating a predetermined functional group in the second resin at a predetermined concentration.

[0011] The present inventors speculate that the reason for solving the above problem is as follows.

[0012] First, by using a crystalline resin having excellent sharp melting properties at low energy and forming a matrix domain structure consisting of a matrix containing a first resin and a domain containing a second resin, excellent low-temperature fixability can be obtained. When the matrix domain structure is not present and the first resin and the second resin are compatible with each other to form a uniform structure, the fixation separation property is likely to decrease. Furthermore, the sharp melting property of the crystalline resin is likely to be lost and the low-temperature fixability is likely to decrease. The melting point Tp of the first resin is preferably 50°C or more and 90°C or less, more preferably 55°C or more and 70°C or less.

[0013] On the other hand, there are three possible ways to improve abrasion resistance. The first is to reduce the friction between the fixed image surface and the abrading material. The second is to increase the cohesive force of the fixed toner layer itself to improve its mechanical strength. The third is to improve the adhesion between the fixed toner layer and recording material such as paper.

[0014] The toner of the present invention has excellent low-temperature fixing properties by forming a matrix domain structure consisting of a matrix containing a first resin, which is a crystalline resin, and a domain containing a second resin, which is an amorphous resin. However, crystalline resins tend to have lower viscoelasticity and lower mechanical strength than amorphous resins. Since the toner of the present invention has a crystalline resin as a matrix, the cohesive force of the toner layer itself is likely to be low, and it is considered that the abrasion resistance may be insufficient. On the other hand, the amorphous resin is considered to be advantageous in terms of abrasion resistance, but since it forms domains, the cohesive force is unlikely to work between the domains, and it is considered that sufficient effects cannot be obtained.

[0015] In the toner of the present invention, calcium carbonate particles are further contained in the domain matrix structure. Furthermore, the monomer unit constituting the second resin made of an amorphous resin forming the domain contains any one of a nitrile group, a carboxy group, and a hydroxy group, thereby controlling the total functional group concentration. It is believed that this causes an interaction between the functional group contained in the domain and the polarized component in the calcium carbonate particle, improving the cohesive force between the domains and providing excellent abrasion resistance.

[0016] Such effects can be obtained when the area ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle is in the range of 35 area % or more and 70 area % or less. When the area ratio of the matrix containing the first resin is less than 35 area %, the above-mentioned matrix domain structure is reversed, and a matrix domain structure consisting of a matrix containing the second resin and a domain containing the first resin may be formed, resulting in a decrease in low-temperature fixability. On the other hand, when the area ratio of the matrix containing the first resin is more than 70 area %, the density of the domain is low, so that the cohesive force between the domains becomes insufficient, and the abrasion resistance is decreased.

[0017] The area ratio of the matrix containing the first resin to the total cross-sectional area of ​​the toner particle is more preferably 40 area % or more and 60 area % or less. The area ratio of the matrix containing the first resin to the total cross-sectional area of ​​the toner particle can be controlled by the amount of the first resin and the second resin charged.

[0018] In the cross-sectional observation of the toner particle, the number-average particle diameter Db of the domain is preferably 50 nm or more and 500 nm or less. When the number-average particle diameter Db of the domain is 500 nm or less, the second resin is easily melted even during low-temperature fixing of the toner, and fixing properties are improved. On the other hand, during high-temperature fixing, the viscosity of the matrix containing the melted first resin is less likely to decrease, and fixing separation properties are improved. In addition, when the number-average particle diameter Db of the domain is 50 nm or more, interaction with calcium carbonate is easily generated, and abrasion resistance is improved. The number-average particle diameter Db of the domain is more preferably 80 nm or more and 430 nm or less.

[0019] The number-average particle diameter Db of the domains can be controlled by the composition of the monomers constituting the crystalline resin, the composition of the monomers constituting the amorphous resin, the manufacturing conditions of the toner particles, etc. Methods for controlling the number-average particle diameter Db of the domains include the relationship between the SP values ​​of the resins constituting the matrix and the domains, the kneading temperature and screw rotation speed in the melt kneading process, and the stirring rotation speed in the aggregation process. If the SP values ​​of the matrix and domain resins are close to each other, the compatibility between the matrix and the domains increases, and the number-average particle diameter of the domains tends to become smaller. In addition, increasing the screw rotation speed or stirring rotation speed increases the shear force on the resin, and the number-average particle diameter of the domains becomes smaller.

[0020] Usable materials are described in detail below.

[0021] <First Resin> The binder resin contains a first resin, and the first resin is a crystalline resin. As the crystalline resin, a known crystalline resin can be used. For example, a crystalline vinyl resin, a crystalline polyester resin, a crystalline polyurethane resin, and a crystalline polyurea resin can be mentioned. In addition, ethylene copolymers such as ethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-methacrylic acid copolymer, and ethylene-acrylic acid copolymer can also be mentioned.

[0022] From the viewpoint of low-temperature fixability, crystalline vinyl resin and crystalline polyester resin are preferred. Also, it may be a hybrid resin in which a vinyl resin and a polyester resin are bonded. The first resin preferably contains a vinyl resin, more preferably is a vinyl resin, and preferably has a first monomer unit represented by the following formula (1). The first resin is preferably a vinyl resin having a monomer unit represented by the following formula (1). The vinyl resin is a polymer or copolymer of a compound containing a group having an ethylenically unsaturated bond such as a vinyl group. Examples of the group having an ethylenically unsaturated bond include a vinyl group, a (meth)allyl group, and a (meth)acryloyl group.

[0023] The content of the first monomer unit in the first resin is preferably 30.0% by mass or more and 90.0% by mass or less, more preferably 45.0% by mass or more and 75.0% by mass or less. The weight average molecular weight (Mw) of the first resin is preferably 5,000 or more and 100,000 or less, more preferably 15,000 or more and 50,000 or less.

[0024] [ka]

[0025] In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms. The first monomer unit represented by the above formula (1) has R 1 The presence of this moiety facilitates the development of crystallinity. The first monomer unit represented by formula (1) is preferably a monomer unit derived from at least one first polymerizable monomer selected from the group consisting of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms.

[0026] Examples of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms include (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myrisyl (meth)acrylate, dotriacontyl (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].

[0027] Among these, from the viewpoint of low temperature fixability, at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with 18 to 36 carbon atoms is preferable, at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with 18 to 30 carbon atoms is more preferable, and at least one selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate is even more preferable. The monomers forming the first monomer unit may be used alone or in combination of two or more kinds.

[0028] SP value of the first monomer unit (J / cm 3 ) 0.5 is SP1, SP1 is preferably less than 20.00, more preferably 19.00 or less, and even more preferably 18.40 or less. The lower limit is not particularly limited, but is preferably 17.00 or more.

[0029] Here, the SP value is an abbreviation for solubility parameter, and is a value that serves as an index of solubility. The calculation method will be described later. The unit of the SP value in the present invention is (J / cm 3 ) 0.5 However, 1 (cal / cm 3 ) 0.5 =0.4888×(J / cm 3) 0.5 by (cal / cm 3 ) 0.5 can be converted to units of

[0030] The first resin preferably has a second monomer unit different from the first monomer unit in the first resin. The SP value of the second monomer unit is expressed as SP2 (J / cm 3 ) 0.5 When SP2 is 30.00 or less, it is preferable that the following relational formula (4) is satisfied, and it is more preferable that the following relational formula (4') is satisfied. There is no particular upper limit for SP2, but it is preferably 30.00 or less. 21.00(J / cm 3 ) 0.5 ≦SP2 (4) 25.00(J / cm 3 ) 0.5 ≦SP2 (4')

[0031] When the SP2 of the second monomer unit satisfies the above formula (4), the second monomer unit has high polarity, and a polarity difference occurs between the first and second monomer units. This polarity difference promotes crystallization of the first monomer unit, thereby obtaining excellent low-temperature fixability. Specifically, the first monomer unit is incorporated into a crystalline resin, and the first monomer units aggregate with each other to exhibit crystallinity.

[0032] Usually, the crystallization of the first monomer unit is inhibited when other monomer units are incorporated, making it difficult for the first monomer unit to exhibit crystallinity as a crystalline resin. However, by setting the SP1 of the first monomer unit and the SP2 of the second monomer unit within the above-mentioned range, it is believed that the first monomer unit and the second monomer unit can form a clear phase-separated state in the first resin without being miscible with each other, and it is believed that the melting point can be easily maintained without reducing the crystallinity.

[0033] Specific examples of the second polymerizable monomer that forms the second monomer unit include the following polymerizable monomers. Preferably, a polymerizable monomer that can form a monomer unit represented by the following formula (2) or (3) is used.

[0034] Monomers having a nitrile group; for example, acrylonitrile, methacrylonitrile, etc.

[0035] Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like.

[0036] Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate.

[0037] Monomers having an amide group; for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (acrylic acid, methacrylic acid, etc.) having an ethylenically unsaturated bond by a known method.

[0038] Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (normal butylamine, t-butylamine, propylamine, isopropylamine, etc.), secondary amine (di-normal ethylamine, di-normal propylamine, di-normal butylamine, etc.), aniline, cycloxylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method, etc.

[0039] [ka] (In formula (2), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. R 3 is a nitrile group (-C≡N), a hydroxyl group, a carboxyl group, Amide group (-C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.31 (R 31 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4) or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4), a urea group (-NH-C(=O)-N(R 33 )2(Two R 33 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms), -COO(CH2)2NHCOOR 34 (R 34 represents an alkyl group having 1 to 4 carbon atoms.) or -COO(CH2)2-NH-C(=O)-N(R 35 )2(Two R 35 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4). R 4 represents a hydrogen atom or a methyl group.

[0040] [ka] (In formula (3), R 5 represents an alkyl group having 1 to 4 carbon atoms, R 6 represents a hydrogen atom or a methyl group.

[0041] Among these, it is preferable to use a monomer having a nitrile group, a hydroxyl group, or a carboxyl group, and among these, acrylonitrile and methacrylonitrile, which are monomers having a nitrile group, are particularly preferable.

[0042] Also preferably used as the second monomer unit are vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octylate. Among these, vinyl esters are preferred from the viewpoint of low-temperature fixability because they are non-conjugated monomers and therefore tend to maintain a suitable reactivity with the first polymerizable monomer and tend to increase the crystallinity of the polymer.

[0043] The content of the second monomer unit in the first resin is preferably 5.0% by mass or more and 40.0% by mass or less, and more preferably 7.0% by mass or more and 30.0% by mass or less.

[0044] The composition may contain a third monomer unit obtained by polymerizing a third polymerizable monomer not included in the range of the above formula (4) (i.e., different from the first polymerizable monomer and the second polymerizable monomer) within a range that does not impair the mass ratio of the above-mentioned first monomer unit and the second monomer unit. As the third polymerizable monomer, a monomer that does not satisfy the above formula (4) can be used among the monomers exemplified as the above-mentioned second polymerizable monomer.

[0045] For example, the following monomers can also be used: styrene and its derivatives such as styrene and o-methylstyrene, and (meth)acrylic acid esters such as methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Among these, the third polymerizable monomer is preferably styrene from the viewpoint of charge diffusion. The content of the third monomer unit in the first resin is preferably 5.0% by mass or more and 50.0% by mass or less, and more preferably 10.0% by mass or more and 35.0% by mass or less.

[0046] In the present invention, the abrasion resistance was improved by incorporating any one of a nitrile group, a carboxy group, and a hydroxy group in the monomer unit constituting the first resin and setting the total functional group concentration to 0.8 mmol / g or more and 10.0 mmol / g or less. By using a nitrile group, a carboxy group, or a hydroxy group as the functional group to be incorporated, both low-temperature fixability and abrasion resistance were achieved. Furthermore, by setting the functional group amount to 0.8 mmol / g or more, interaction with calcium carbonate particles was obtained, improving abrasion resistance. On the other hand, by setting it to 10.0 mmol / g or less, low-temperature fixability could be maintained. Among them, the nitrile group provided an excellent effect on abrasion resistance.

[0047] <Second resin> The binder resin contains a second resin, and the second resin is an amorphous resin. The second resin forming the domain can be a known amorphous resin, and is preferably a polyester resin, a styrene-acrylic resin, or a hybrid resin thereof from the viewpoint of low-temperature fixing property and abrasion resistance. As the styrene-acrylic resin, a styrene-acrylic resin that is usually used in a toner can be suitably used.

[0048] In the present invention, the monomer unit constituting the second resin contains any one of a nitrile group, a carboxy group, and a hydroxy group, and the total functional group concentration is set to 0.8 mmol / g or more and 10.0 mmol / g or less, thereby obtaining the effects of the present invention. By using a nitrile group, a carboxy group, or a hydroxy group, it is possible to improve low-temperature fixing property and abrasion resistance. In addition, by making the functional group 0.8 mmol / g or more, an interaction with calcium carbonate particles is obtained, and abrasion resistance is obtained. On the other hand, by making it 10.0 mmol / g or less, it is possible to achieve both low-temperature fixing property and abrasion resistance. Among them, the nitrile group has an excellent effect on abrasion resistance.

[0049] The second resin preferably contains a styrene-acrylic resin, which is a vinyl resin, and is more preferably a styrene-acrylic resin. The styrene-acrylic resin is preferably a copolymer of a styrene-based monomer and a (meth)acrylic monomer. The weight average molecular weight (Mw) of the second resin is preferably 10,000 or more and 100,000 or less, and more preferably 20,000 or more and 60,000 or less.

[0050] Examples of styrene monomers include styrene, α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene. These styrene monomers can be used alone or in combination.

[0051] Examples of the (meth)acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-amyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, dimethyl phosphate ethyl (meth)acrylate, diethyl phosphate ethyl (meth)acrylate, dibutyl phosphate ethyl (meth)acrylate, and 2-benzoyloxyethyl (meth)acrylate, (meth)acrylonitrile, 2-hydroxyethyl (meth)acrylate, (meth)acrylic acid, and maleic acid. These (meth)acrylic monomers can be used alone or in combination.

[0052] As the polyester resin, a polyester resin that is usually used in a toner can be suitably used. As a monomer used in the polyester resin, a polyhydric alcohol (a divalent or trivalent or higher alcohol), a polyvalent carboxylic acid (a divalent or trivalent or higher carboxylic acid), an acid anhydride thereof, or a lower alkyl ester thereof can be mentioned.

[0053] Examples of polyhydric alcohols include the following: Examples of dihydric alcohols include the following bisphenol derivatives: polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane, etc.

[0054] Other polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. These polyhydric alcohols can be used alone or in combination.

[0055] Examples of polyvalent carboxylic acids include the following. Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.

[0056] Examples of trivalent or higher carboxylic acids, their acid anhydrides, and their lower alkyl esters include the following: 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their acid anhydrides, and their lower alkyl esters.

[0057] Among these, 1,2,4-benzenetricarboxylic acid (trimellitic acid) or its derivatives such as anhydride are preferably used because they are inexpensive and the reaction can be easily controlled. These polyvalent carboxylic acids can be used alone or in combination.

[0058] <Other resins> The binder resin may contain a third resin other than the first and second resins to such an extent that the effect of the present invention is not impaired, for the purpose of improving pigment dispersibility, etc. Examples of such resins include the following: polyvinyl chloride, phenolic resin, natural resin-modified phenolic resin, natural resin-modified maleic acid resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, and petroleum-based resin.

[0059] <Calcium carbonate particles> The toner particles of the present invention contain calcium carbonate particles in the toner particles at 1% by mass or more and 15% by mass or less. Specifically, in the observation of the cross section of the toner particles, the calcium carbonate particles are present in a region 100 nm inside from the outline of the cross section of the toner particles. Since calcium carbonate particles have a polarizing component, it is considered that by including them in the toner particles, the calcium carbonate particles interact with the functional groups of the domains to improve the cohesive force of the toner layer on a medium such as thick coated paper, thereby improving the abrasion resistance. In addition, since the calcium carbonate particles have a refractive index close to that of a general resin used in toners, the effect on light scattering can be reduced. Therefore, even if a relatively large amount of calcium carbonate is included, the effect on the color can be reduced. Note that, when the content is lower than 1% by mass, there are few calcium carbonate particles that contribute to the interaction with the domains, so sufficient effect on the abrasion resistance cannot be obtained. When the content is higher than 15% by mass, there are too many calcium carbonate particles, so the abrasion resistance may be deteriorated.

[0060] The particle size of the calcium carbonate particles contained in the toner particles of the present invention is preferably in the range of 100 nm to 500 nm. If it is smaller than 100 nm, the calcium carbonate particles tend to aggregate, making it difficult to obtain the effect of improving abrasion resistance. On the other hand, if it is larger than 500 nm, the number of calcium carbonate particles becomes small, making it difficult to obtain the effect of improving abrasion resistance.

[0061] In a more preferred embodiment, the calcium carbonate particles contained in the toner particles of the present invention are coated with a fatty acid. Although known fatty acids can be used, linear saturated fatty acids having 8 to 28 carbon atoms, such as nonanoic acid, lauric acid, stearic acid, and cerotic acid, are preferred. Since calcium carbonate particles coated with a fatty acid are more compatible with crystalline resins and more likely to exist between domains, it is believed that the cohesive force between domains can be easily improved. The amount of fatty acid coated is preferably in the range of 0.1% by mass to 5% by mass.

[0062] In addition, it is considered that the interaction is easier when the number average particle diameter Da of the calcium carbonate particles and the number average particle diameter Db of the domains are approximately the same size, and excellent effects were obtained. By setting the ratio Da / Db of the number average particle diameter Da of the calcium carbonate particles to the number average particle diameter Db of the domains in the range of 0.25 to 2.00 as a preferable range, excellent abrasion resistance was obtained.

[0063] <Release agent> The toner contains a release agent. It is advisable to select and use an optimal release agent in combination with the first resin and the second resin. It is considered that the release agent migrates to the toner particle surface via the first resin during fixing. Therefore, it is preferable that the melting point of the release agent is equal to or higher than the melting point Tp of the first resin and equal to or lower than the softening temperature Tm of the second resin. Examples of the release agent include the following. Note that wax is synonymous with release agent.

[0064] Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.

[0065] Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene saturated fatty acid bisamides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxy groups obtained by hydrogenation of vegetable oils and fats.

[0066] The release agent preferably contains a hydrocarbon wax, and the content of the wax is preferably 2.0 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the binder resin.

[0067] <Coloring agent> The toner particles may contain a colorant as required. Examples of the colorant include the following. Examples of the black colorant include carbon black, and a colorant toned to black using a yellow colorant, a magenta colorant, and a cyan colorant. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity in terms of the image quality of a full-color image.

[0068] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.

[0069] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.

[0070] Pigments for cyan toner include: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45, copper phthalocyanine pigments with 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. An example of a dye for cyan toner is CI Solvent Blue 70.

[0071] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.

[0072] These colorants can be used alone or in combination, or in the form of a solid solution. The colorant is selected in terms of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner. The content of the colorant is preferably 0.1 parts by mass or more and 30.0 parts by mass or less per 100 parts by mass of the binder resin.

[0073] <Charge control agent> The toner particles may contain a charge control agent as necessary. By blending a charge control agent, the charge characteristics can be stabilized, and the amount of triboelectric charge can be optimally controlled according to the development system. As the charge control agent, a known one can be used, but in particular, a metal compound of an aromatic carboxylic acid is preferred, which is colorless, has a high charging speed of the toner, and can stably maintain a constant amount of charge.

[0074] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.

[0075] The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, more preferably 0.5 parts by mass to 10.0 parts by mass, based on 100 parts by mass of the binder resin.

[0076] <Other inorganic particles> The toner may contain inorganic fine particles as required. The inorganic fine particles may be added internally to the toner particles, or may be mixed with the toner as an external additive. Examples of inorganic fine particles include silica fine particles, titanium oxide fine particles, alumina fine particles, and composite oxide fine particles thereof. Among the inorganic fine particles, silica fine particles and titanium oxide fine particles are preferred for improving flowability and uniform charging. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.

[0077] From the viewpoint of improving fluidity, inorganic fine particles as external additives should have a specific surface area of ​​50 m 2 / g or more 400m 2 From the viewpoint of improving durability and stability, the inorganic fine particles as the external additive preferably have a specific surface area of ​​10 m 2 / g or more 50m 2 In order to achieve both improved fluidity and durability and stability, inorganic fine particles having a specific surface area within the above range may be used in combination.

[0078] The content of the external additive is preferably 0.1 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the toner particles. The toner particles and the external additive can be mixed using a known mixer such as a Henschel mixer.

[0079] <Developer> The toner can be used as a one-component developer, but it is more preferable to mix the toner with a magnetic carrier and use it as a two-component developer, in that stable images can be obtained over a long period of time.

[0080] Examples of magnetic carriers that can be used include generally known magnetic carriers such as iron powder with an oxidized surface, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, and rare earth elements, alloy particles thereof, oxide particles, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.

[0081] When the toner is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio, in terms of the toner concentration in the two-component developer, is preferably 2.0% by mass or more and 15.0% by mass or less, and more preferably 4.0% by mass or more and 13.0% by mass or less.

[0082] <Toner manufacturing method> The method for producing the toner is not particularly limited, and a known production method can be used. The melt-kneading / pulverization method is preferably used. The melt-kneading / pulverization method includes, for example, a melt-kneading step of melt-kneading a composition containing a binder resin and a release agent to obtain a melt-kneaded product, and a pulverization step of cooling and solidifying the melt-kneaded product, and pulverizing the cooled and solidified product to obtain a pulverized product.

[0083] The procedure for producing the toner using the melt-kneading pulverization method will be described below.

[0084] <Raw material mixing process> In the raw material mixing process, materials constituting the toner particles, such as binder resin, calcium carbonate particles, and a release agent, as well as other components such as colorants and charge control agents as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include a double cone mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.).

[0085] <Melting and kneading process> Next, the mixed materials are melt-kneaded to disperse the release agent in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with two rolls or the like and cooled with water or the like in a cooling process.

[0086] <Crushing process> The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.

[0087] <Classification process> Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).

[0088] <External addition process> The obtained toner particles may be used as a toner as it is. If necessary, an external additive may be added to the surface of the toner particles to form a toner. As a method for adding an external additive, a method may be mentioned in which the classified toner and various known external additives are mixed in a predetermined amount, and stirred and mixed using a mixing device such as a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external additive machine.

[0089] The methods for measuring various physical properties are described below.

[0090] <Evaluation of matrix domain structure by cross-sectional observation of toner> First, a thin slice is prepared as a reference sample for the amount present. The first resin, which is a crystalline resin, is thoroughly dispersed in a visible light curable resin (Aronix LCR Series D800), and then irradiated with short wavelength light to harden it. The obtained hardened material is cut with an ultramicrotome equipped with a diamond knife to prepare a thin slice sample of 250 nm. In the same manner, a thin slice sample is also prepared for the second resin, which is an amorphous resin.

[0091] In addition, the first resin and the second resin are mixed at 30 / 70 and 70 / 30 by mass, and melt-kneaded to prepare a kneaded product. These are also dispersed in a visible light curable resin, cured, and then cut out to prepare thin-section samples. Next, the cut-out samples are observed at the cross section of these reference samples using a transmission electron microscope (JEM-2800 electron microscope manufactured by JEOL Ltd.) (TEM-EDX), and element mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen. The mapping conditions are as follows: Accelerating voltage: 200 kV Electron beam irradiation size: 1.5 nm Live time limit: 600sec Dead time: 20~30 Mapping resolution: 256×256

[0092] Based on the spectral intensity (average in an area of ​​10 nm square) of each element, calculate (oxygen element intensity / carbon element intensity) and (nitrogen element intensity / carbon element intensity) and create a calibration curve for the mass ratio of the first resin to the second resin. If the monomer unit of the first resin contains nitrogen atoms, the calibration curve of (nitrogen element intensity / carbon element intensity) will be used for future quantification.

[0093] Next, the toner sample is analyzed. After the toner is thoroughly dispersed in a visible light curable resin (Aronix LCR Series D800), it is irradiated with short wavelength light and cured. The resulting cured product is cut out using an ultramicrotome equipped with a diamond knife to prepare a 250 nm thin sample. The cut out sample is then observed using a transmission electron microscope (JEOL JEM-2800) (TEM-EDX). A cross-sectional image of the toner particle is obtained, and elemental mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen.

[0094] The toner particle cross section to be observed is selected as follows. First, the cross-sectional area of ​​the toner particle is obtained from the toner particle cross-sectional image, and the diameter (equivalent circle diameter) of a circle having an area equal to the cross-sectional area is obtained. Only toner particle cross-sectional images in which the absolute value of the difference between this equivalent circle diameter and the weight average particle diameter (D4) of the toner particles is within 1.0 μm are observed. For the domains confirmed in the observed image, (oxygen element intensity / carbon element intensity) and / or (nitrogen element intensity / carbon element intensity) are calculated based on the (average of 10 nm square) spectral intensity of each element, and the ratio of the first resin to the second resin is calculated by comparing with the calibration curve. Domains in which the ratio of the second resin is 80% or more are defined as the domains of the present invention.

[0095] After identifying the domains confirmed by the observed image, a binarization process is performed. The binarized image is analyzed to determine the major axis of the domains present in the cross-sectional image of the toner particle. This is measured at 10 points per toner particle, and the arithmetic average of the major axis of the domains of the 10 toner particles is taken as the number-average diameter (nm) of the domains.

[0096] Meanwhile, the area of ​​the domains is calculated by adding up the areas of all the domains present in one toner particle cross-sectional image to obtain the total area, which is designated as S1. The total area of ​​the domains of 100 toner particles (i.e., S1 + S2... + S100) is calculated, and the arithmetic average value of the 100 particles is designated as the "domain area."

[0097] Regarding the cross-sectional area of ​​the toner particles, the sum of the cross-sectional areas of the toner particles (for 100 toner particles) calculated from the toner cross-sectional images used to calculate the area of ​​the domains is calculated, and the arithmetic average value is defined as the "total cross-sectional area of ​​the toner particles." The "total cross-sectional area of ​​the toner particles" minus the "area of ​​the domain" is defined as the "area of ​​the matrix." The area ratio of the matrix to the total cross-sectional area of ​​the toner particles (area ratio of the matrix (%)) is defined as [area of ​​the matrix] / [total cross-sectional area of ​​the toner particles] x 100. The image processing software "ImageJ" is used for the binarization process and the calculation of the number-average diameter of the domains and the standard deviation of the longitudinal angle of the domains.

[0098] <Method of separating each material from toner> By utilizing the difference in solubility of each material contained in the toner in a solvent, each material can be separated from the toner.

[0099] First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble portion (second resin) is separated from the insoluble portion (first resin, release agent, colorant, inorganic fine particles, etc.).

[0100] Second separation: The insoluble matter obtained in the first separation (first resin, release agent, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (first resin, release agent) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated.

[0101] Third separation: The soluble fraction (first resin, release agent) obtained in the second separation is dissolved in chloroform at 23° C., and the soluble fraction (first resin) and the insoluble fraction (release agent) are separated.

[0102] Fourth separation: The insoluble matter obtained in the second separation is dispersed in tetrahydrofuran, and by changing the centrifugal force in the centrifuge method, calcium carbonate and colorant are separated due to the difference in specific gravity.

[0103] (When a third resin is included) First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin, third resin) is separated from the insoluble matter (first resin, release agent, colorant, inorganic fine particles, etc.).

[0104] Second separation: The soluble fraction (second resin, third resin) obtained in the first separation is dissolved in toluene at 23° C., and the soluble fraction (third resin) is separated from the insoluble fraction (second resin).

[0105] Third separation: The insoluble matter obtained in the first separation (first resin, release agent, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (first resin, release agent) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated.

[0106] Fourth separation: The soluble fraction (first resin, release agent) obtained in the third separation is dissolved in chloroform at 23° C., and the soluble fraction (first resin) and the insoluble fraction (release agent) are separated.

[0107] Fifth separation: The insoluble matter obtained in the third separation is dispersed in tetrahydrofuran, and by changing the centrifugal force in the centrifuge method, calcium carbonate and colorant are separated due to the difference in specific gravity.

[0108] <Calcium carbonate particle content> The content of calcium carbonate particles is calculated from the amount of calcium carbonate particles separated from the toner particles by the above-mentioned method.

[0109] <Particle size of calcium carbonate particles> The number-average particle size of calcium carbonate particles is calculated by observing the cross section of a toner particle with a scanning electron microscope (S-4800, Hitachi High-Technologies Corporation), measuring the major axis of 100 particles, and calculating the average value.

[0110] <Structure of surface treatment material for calcium carbonate particles> The structure was analyzed by pyrolysis gas chromatography mass spectrometry (GC-MS) as follows. 300 μg of calcium carbonate separated from the toner particles by the above method was embedded in the following Pyrofoil F590 and introduced into a pyrolysis furnace, heated at 590°C for 5 seconds in an inert (helium) atmosphere, and the generated decomposition gas was introduced into the gas chromatograph inlet, and the following oven profile was performed. The column outlet was connected to an MS analyzer via a transfer line, and a total ion chromatogram (TIC) was obtained by plotting the ion current on the vertical axis and the retention time on the horizontal axis. Next, mass spectra were extracted from all detected peaks in the obtained chromatogram using the attached software, and the compounds were assigned based on the NIST-2017 database.

[0111] The measuring device and measuring conditions are as follows. Pyrolysis furnace: Japan Analytical Industry JSP900 (manufactured by Japan Analytical Industry) Pyrofoil: F590 (manufactured by Japan Analytical Industry Co., Ltd.) GC:Agilent Technologies 7890A GC MS: Agilent Technologies 5975C Column: HP-5ms 30 m, inner diameter 0.25 mm, mobile phase thickness 0.25 μm (Agilent) Carrier gas: He (purity 99.9995% or higher) Oven profile: (1) hold temperature at 40°C for 3 minutes, (2) increase temperature to 320°C at 10°C / min, (3) hold temperature at 320°C for 20 minutes Inlet temperature: 280℃ Split ratio: 50:1 Column flow rate: 1mL / min (quantitative) Transfer line temperature: 280℃ Observation MS range: 30-600 Da Ionization: EI 70eV Ion source temperature: 280℃ Quadrupole temperature: 150℃

[0112] <Amount of surface treatment material for calcium carbonate particles> The calcium carbonate particles separated from the toner particles by the above method were measured using a thermogravimetric-differential thermal analyzer (manufactured by Rigaku, differential thermal balance TG-DTA, ThermoPlus TG8120). The temperature was raised from 25 °C to 400 °C at a rate of 10 °C / min, and the amount of the surface treatment agent was measured from the weight change.

[0113] <Calculation method of SP value> The SP value is determined as follows according to the calculation method proposed by Fedors. For each polymerizable monomer, the evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm 3 / mol) are obtained from the table described in "Polym. Eng. Sci., 14(2), 147-154(1974)" for the atoms or atomic groups in the molecular structure, and (4.184×ΣΔei / ΣΔvi) 0.5 is taken as the SP value (J / cm 3 ). Note that the SP value of the monomer unit is calculated by the same calculation method as above for the atoms or atomic groups in the molecular structure in the state where the double bond of the polymerizable monomer is cleaved by polymerization. 0.5

[0114] <Functional group concentration of binder resin> (Sample preparation) 100 mg of the binder resin sample separated by the above method was weighed into an NMR sample tube, 10 mg of sodium trimethylsilylpropane sulfonate as an internal standard substance, and 10 mg of Cr(AcAc)3 as a relaxation reagent were weighed, and 0.45 ml of a deuterated solvent (for example, deuterated pyridine) was added to dissolve the sample sufficiently.

[0115] (Measurement conditions) Apparatus: "AVANCE III HD400" manufactured by Bruker BioSpin Number of integrations: 24000 times

[0116] (Analysis and calculation) ​The functional group concentration (mmol / g) is calculated from the peak area ratio of carbon derived from nitrile groups, carboxy groups, and hydroxy groups of the binder resin sample to the peak area of ​​carbon derived from methyl groups.

[0117] <Method for measuring weight average molecular weight (Mw) of resins, etc. using gel permeation chromatography (GPC)> The weight average molecular weight (Mw) of tetrahydrofuran (THF) soluble matter such as resin is measured by gel permeation chromatography (GPC) as follows. First, a sample such as resin is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The obtained solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of the THF soluble component is about 0.8 mass %. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko) Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Oven temperature: 40.0℃ Sample injection volume: 0.10 mL

[0118] In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (product names: "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.

[0119] <Measuring method for melting point, endothermic peak and endothermic amount of resin, etc.> The melting point of a resin or the like, as well as the endothermic peak and endothermic amount, are measured using a DSC Q1000 (manufactured by TA Instruments) under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃

[0120] The melting points of indium and zinc are used to correct the temperature of the detector, and the heat of fusion of indium is used to correct the amount of heat. Specifically, approximately 5 mg of sample is precisely weighed and placed in an aluminum pan, and differential scanning calorimetry is performed. An empty silver pan is used as a reference. The peak temperature of the maximum endothermic peak in the first heating process is taken as the melting point. Note that the maximum endothermic peak is the peak with the largest amount of endothermic heat when there are multiple peaks. The amount of endothermic heat of the maximum endothermic peak is then calculated.

[0121] <Method of measuring resin softening point (Tm)> The softening point of the resin is measured using a constant load extrusion type capillary rheometer "Flow characteristic evaluation device Flow Tester CFT-500D" (manufactured by Shimadzu Corporation) according to the manual that comes with the device. With this device, a constant load is applied from above the measurement sample by a piston, while the measurement sample filled in a cylinder is heated and melted, and the molten measurement sample is extruded from a die at the bottom of the cylinder, and a flow curve showing the relationship between the piston descent amount and temperature at this time can be obtained. The "melting temperature in the 1 / 2 method" described in the manual that comes with the "Flow characteristic evaluation device Flow Tester CFT-500D" is taken as the softening point. The melting temperature in the 1 / 2 method is calculated as follows.

[0122] First, find 1 / 2 of the difference between the amount of piston descent at the time when the outflow ends (end of outflow, Smax) and the amount of piston descent at the time when the outflow starts (minimum point, Smin) (this is X. X=(Smax-Smin) / 2). Then, the temperature of the flow curve when the amount of piston descent is the sum of X and Smin is the melting temperature in the 1 / 2 method. The measurement sample is a cylindrical shape with a diameter of about 8 mm, compressed and molded at about 10 MPa for about 60 seconds using a tablet molding compressor (for example, NT-100H, manufactured by NPA Systems Co., Ltd.) in an environment of 25°C. Specific operations in the measurement are performed according to the manual attached to the device. The measurement conditions for CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 50℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 10.0kgf / cm 2 (0.9807MPa) Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm

[0123] <Method of measuring weight-average particle size (D4) of toner (particles)> The weight-average particle diameter (D4) of the toner (particles) is measured with a precision particle size distribution measuring device using the pore electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), for setting measurement conditions and analyzing measurement data, with an effective measurement channel count of 25,000, and the measurement data is analyzed and calculated. The electrolyte solution used for the measurement is one in which special grade sodium chloride is dissolved in ion-exchanged water to a concentration of approximately 1 mass%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before performing the measurement and analysis, the dedicated software is set up as follows.

[0124] In the "Change Standard Measurement Method (SOM) Screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (manufactured by Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to Particle Size Conversion Setting Screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bin, and the particle size range to 2 μm to 60 μm. The specific measurement method is as follows. (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Approximately 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and approximately 0.3 mL of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 mL of Conaminon N is added to this water tank. (4) Set the beaker (2) in the beaker fixing hole of the ultrasonic disperser, operate the ultrasonic disperser, and adjust the height of the beaker so that the resonance state of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolytic solution (5) in which the toner (particles) is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4). EXAMPLES

[0125] The basic configuration and features of the present invention have been described above, and the present invention will be specifically described below based on examples. However, the present invention is not limited to these. Note that parts are by weight unless otherwise specified.

[0126] <Production Example of First Resin 1 (Crystalline Resin 1)> Solvent: toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of behenyl acrylate and styrene in the ratio shown below.) (Behenyl acrylate 60.0 parts) (Styrene 30.0 parts) Polymerization initiator 0.5 parts [t-Butyl peroxypivalate (NOF Corp.: Perbutyl PV)] The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 70°C while stirring at 200 rpm, and a polymerization reaction was carried out for 12 hours to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. The solution was then cooled to 25°C, and then the solution was poured into 1000.0 parts of methanol while stirring to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered, washed with methanol, and vacuum dried at 40°C for 24 hours to obtain a first resin 1 (crystalline resin 1). The weight average molecular weight (Mw) of the first resin 1 (crystalline resin 1) was 34000, and the melting point (Tp) was 61°C.

[0127] When the first resin 1 (crystalline resin 1) was analyzed by NMR, it was found to contain 60.0 parts by mass of a monomer unit derived from behenyl acrylate and 30.0 parts by mass of a monomer unit derived from styrene. The SP value (unit: (J / cm 3 ) 0.5 ) was calculated.

[0128] <Production Examples of First Resins 2 to 9 (Crystalline Resins 2 to 9)> In the production example of the first resin 1 (crystalline resin 1), the reaction was carried out in the same manner except that the polymerizable monomers and the mass parts thereof were changed as shown in Table 1, to obtain the first resins 2 to 9 (crystalline resins 2 to 9).

[0129] [Table 1] The abbreviations in Table 1 are as follows. The numbers in parentheses indicate the SP value (J / cm) when the monomer unit was formed. 3 ) 0.5 It is. BEA: Behenyl acrylate (SP value: 18.3) St: Styrene (SP value: 20.1) AN: Acrylonitrile (SP value: 29.4) AA: Acrylic acid (SP value: 28.7) 2-HEA: 2-hydroxyethyl acrylate (SP value: 29.6)

[0130] <Production Example of First Resin 10 (Crystalline Resin 10)> 1,12-dodecanediol: 46.5 parts Dodecanedioic acid: 53.3 parts Tin 2-ethylhexanoate: 0.5 parts The above materials were weighed into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen introduction tube, and a thermocouple. After replacing the inside of the flask with nitrogen gas, the temperature was gradually raised while stirring, and the reaction was carried out for 3 hours while stirring at a temperature of 140°C. Next, the pressure in the reaction vessel was reduced to 8.3 kPa, and the reaction was carried out for 4 hours while maintaining the temperature at 200°C. Thereafter, the pressure in the reaction vessel was reduced to 5 kPa or less, and the reaction was carried out at 200°C for 3 hours, thereby obtaining crystalline resin 10. The weight average molecular weight (Mw) of the first resin 10 (crystalline resin 10) was 20,000, and the melting point (Tp) was 71°C.

[0131] <Production Example of Second Resin 1 (Amorphous Resin 1)> 50.0 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 185 ° C. in a sealed state under stirring. A mixed solution of 80.0 parts of styrene, 19.0 parts of n-butyl acrylate, 1.0 parts of divinylbenzene, and 1.5 parts of di-tert-butyl peroxide and 20.0 parts of xylene was continuously dropped into the autoclave for 3 hours while controlling the temperature inside the autoclave to 185 ° C., and polymerization was performed. The temperature was further maintained for 1 hour to complete the polymerization, and the solvent was removed to obtain a second resin 1 (amorphous resin 1). The weight average molecular weight (Mw) of the second resin 1 (amorphous resin 1) was 45,000, and the softening point (Tm) was 103 ° C.

[0132] <Production Examples of Second Resins 2 to 7 (Amorphous Resins 2 to 7)> In the production example of the second resin 1 (crystalline resin 1), the reaction was carried out in the same manner except that the polymerizable monomers and the mass parts thereof were changed as shown in Table 2, to obtain the second resins 2 to 7 (amorphous resins 2 to 7).

[0133] [Table 2] The abbreviations in Table 2 are as follows. The numbers in parentheses indicate the SP value (J / cm) when the monomer unit was formed. 3 ) 0.5 It is. St: Styrene (SP value: 20.1) n-BA: n-butyl acrylate (SP value: 20.0) DVB: Divinylbenzene (SP value: 24.3) AN: Acrylonitrile (SP value: 29.4) AA: Acrylic acid (SP value: 28.7) 2-HEA: 2-hydroxyethyl acrylate (SP value: 29.6)

[0134] <Production Example of Second Resin 8 (Amorphous Resin 8)> (Polyester resin 1 formulation) Bisphenol A ethylene oxide (2.2 mol adduct) 50.0 mol parts Bisphenol A propylene oxide (2.2 mol adduct) 50.0 mol parts Terephthalic acid 65.0 mol parts Trimellitic anhydride 25.0 mol parts Acrylic acid 10.0 mol parts 60 parts of the mixture of monomers that produce the polyester resin 1 was charged into a four-neck flask, and the flask was equipped with a pressure reducing device, a water separator, a nitrogen gas introducing device, a temperature measuring device, and a stirring device, and stirred at 160 ° C. under a nitrogen atmosphere. 40 parts of vinyl polymerizable monomers (styrene 80.0 parts, acrylate-n-butyl 19.0 parts, acrylic acid 30.0 parts, divinylbenzene 1.0 parts) that produce a vinyl resin and 1 part of benzoyl peroxide as a polymerization initiator were dropped from a dropping funnel over 4 hours, and reacted at 160 ° C. for 5 hours. The mixture was then heated to 230 ° C., and 0.2 parts of titanium tetrabutoxide was added relative to the total amount of monomers that produce the polyester resin, and polymerization was carried out until the softening point reached 115 ° C. After the reaction was completed, the mixture was removed from the vessel, cooled, and pulverized to obtain a second resin 8 (amorphous resin 8). The second resin 8 (amorphous resin 8) had a weight average molecular weight (Mw) of 25,000 and a softening point (Tm) of 115°C.

[0135] <Production of calcium carbonate 1> Put the following ingredients into a Henschel mixer. Light calcium carbonate particles (average particle size: 200 nm) 100 parts Stearic acid 2 parts After stirring at 2000 rpm for 2 minutes, the mixture was heated to 120° C. and stirred at 100 rpm for 10 minutes to obtain calcium carbonate 1.

[0136] <Production of calcium carbonate 2-7> Calcium carbonates 2 to 7 were obtained in the same manner as in the production method for calcium carbonate 1, except that the material was changed to precipitated calcium carbonate particles having a number average diameter shown in Table 3 and the surface treatment material was also changed.

[0137] [Table 3]

[0138] <Production Example of Toner Particle 1 and Toner 1> ·Crystalline resin 3 50.0 parts Amorphous resin 3 50.0 parts 5.0 parts wax 1 (Fischer-Tropsch wax; melting point 90°C) Colorant 1 9.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) The above materials were mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s -1 After mixing for a rotation time of 5 minutes, the mixture was kneaded in a twin-screw kneader (PCM-30 model, manufactured by Ikegai Corporation) set at a temperature of 130°C with a screw rotation speed of 250 rpm and a discharge temperature of 130°C.

[0139] The mixture was coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The obtained coarsely crushed product was finely crushed using a mechanical crusher (T-250, manufactured by Freund Turbo Co., Ltd.). It was then classified using a Faculty F-300 (manufactured by Hosokawa Micron Co., Ltd.) to obtain toner particles 1 having a weight average particle size of about 6.0 μm. The classification operation conditions were a classification rotor rotation speed of 130 s -1 , Distributed rotor speed 120s -1 It was decided.

[0140] For 100 parts of toner particles, the surface is treated with 4% by mass of hexamethyldisilazane to obtain a BET specific surface area of ​​25 m 2 / g hydrophobic silica fine particles, 0.5 parts, BET specific surface area 100 m 2 0.5 parts of hydrophobic silica particles / g were added, and the mixture was mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 30 s -1 The mixture was mixed for 10 minutes with a rotation time of 10 minutes to obtain Toner 1.

[0141] <Production Examples of Toner Particles 2 to 39 and Toners 2 to 39> Toner particles 2 to 39 were obtained by carrying out the same production procedure as in the production example of toner particle 1, except that the types and amounts of the crystalline resin, amorphous resin, calcium carbonate particles, and release agent, and the rotation speed during kneading were changed to the conditions shown in Table 4. Furthermore, the same external additives as in toner 1 were added to each toner, thereby obtaining toners 2 to 39.

[0142] However, toner 16 was produced by externally adding 8.0 parts of calcium carbonate particles 3 to 100 parts of toner particles 16 together with the above hydrophobic silica microparticles after the production of toner particles 16, rather than during kneading (internal addition).

[0143] The number average diameter Da of the calcium carbonate particles of the produced toner particles 1 to 39 was evaluated based on the above-mentioned method. The cross-section of the toner was observed to evaluate the matrix domain structure, the area ratio of the matrix, and the number average diameter Db of the domains. The ratio Da / Db of the number average diameter Da of the calcium carbonate to the number average diameter Db of the domains was calculated. The type and amount of functional groups of the amorphous resin and the type and amount of functional groups of the crystalline resin were evaluated. The ratio of the monomer unit represented by formula (1) to the total mass of all monomer units in the crystalline resin was evaluated. The evaluation results are shown in Table 5.

[0144] The area ratio of the matrix of the toner particle 12 is the area ratio when the matrix is ​​made of an amorphous resin.

[0145] [Table 4] The abbreviations in Table 4 are as follows: Wax 2: (Fischer-Tropsch wax; melting point 70°C) Wax 3: Behenyl behenate

[0146] [Table 5]

[0147] <Magnetic Carrier 1 Manufacturing Example> Number average particle size: 0.30μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 1 Number average particle size: 0.50μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 2 To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and the mixture was mixed and stirred at high speed in a container at 100° C. or higher to treat each of the fine particles.

[0148] Phenol: 10% by weight Formaldehyde solution: 6% by mass (40% by mass of formaldehyde, 10% by mass of methanol, 50% by mass of water) Magnetite treated with the above silane compound 1:58 mass% Magnetite treated with the above silane compound 2: 26% by mass 100 parts of the above material, 5 parts of 28% by mass aqueous ammonia, and 20 parts of water were placed in a flask, and the temperature was raised to 85°C in 30 minutes and held while stirring and mixing, and polymerization reaction was carried out for 3 hours to harden the resulting phenolic resin. The hardened phenolic resin was then cooled to 30°C, and water was added, after which the supernatant liquid was removed, and the precipitate was washed with water and then air-dried. This was then dried at a temperature of 60°C under reduced pressure (5 mmHg or less) to obtain spherical magnetic carrier 1 with magnetic material dispersion. The 50% particle size (D50) based on volume of magnetic carrier 1 was 34.2 μm.

[0149] <Production example of two-component developer 1> Toner 1 (8.0 parts) was added to magnetic carrier 1 (92.0 parts), and mixed in a V-type mixer (V-20, manufactured by Seishin Enterprises) to obtain two-component developer 1.

[0150] <Production Examples of Two-Component Developers 2 to 39> Two-component developers 2 to 39 were obtained by carrying out the same production procedure as in the production example of two-component developer 1, except that toner 1 was changed to toners 2 to 39, respectively.

[0151] Example 1 The evaluation was carried out using the above-mentioned two-component developer 2. A modified Canon digital commercial printing printer imageRUNNER ADVANCE C5560 was used as the image forming apparatus, and two-component developer 2 was placed in the cyan developer. The apparatus was modified so that the fixing temperature, process speed, direct current voltage VDC of the developer carrier, charging voltage VD of the electrostatic latent image carrier, and laser power could be freely set.

[0152] The image output evaluation was performed by outputting a FFh image (solid image) with the desired image ratio, adjusting VDC, VD, and laser power so that the amount of toner on the FFh image on the paper was the desired amount, and performing the evaluation described below. FFh is a value that expresses 256 gradations in hexadecimal, with 00h being the first gradation (white background) of the 256 gradations and FFh being the 256th gradation (solid area) of the 256 gradations. Evaluation was performed based on the following evaluation method, and the results are shown in Table 6.

[0153] [Low temperature fixability] ·Paper: GFC-081 (81.0g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner load on paper: 0.70mg / cm 2 (Adjusted by DC voltage VDC of developer carrier, charging voltage VD of electrostatic latent image carrier, and laser power) Evaluation image: Place a 2cm x 5cm image in the center of the A4 paper. Test environment: Low temperature and low humidity environment (temperature 15℃ / humidity 10% RH (hereinafter referred to as "L / L")) Fixing temperature: 140℃ Process speed: 400mm / sec

[0154] The above evaluation image was output, and the low-temperature fixability was evaluated. The value of the image density reduction rate was used as an evaluation index for the low-temperature fixability. The image density reduction rate was measured using an X-Rite color reflection densitometer (500 series: manufactured by X-Rite Corporation) by first measuring the image density at the center. Next, the part where the image density was measured was subjected to pressure of 4.9 kPa (50 g / cm 2 The fixed image was rubbed (five times back and forth) with Silbon paper under a load of 1000 g / m2, and the image density was measured again. The image density reduction rate before and after the rub was calculated using the following formula. The obtained image density reduction rate was evaluated according to the following evaluation criteria. Image density decrease rate=(image density before friction−image density after friction) / (image density before friction)×100

[0155] (Evaluation Criteria) AA: Image density reduction rate is less than 1.0% A: Image density reduction rate: 1.0% to less than 3.0% B: Image density reduction rate: 3.0% or more and less than 5.0% C: Image density reduction rate: 5.0% or more and less than 8.0% D: Image density reduction rate 8.0% or more

[0156] [Abrasion resistance] Paper: OK Topcoat Matte N157 (157.0 g / m 2 ) (Coated cardboard sold by Oji Paper Co., Ltd., uses calcium carbonate as a coating material) Toner load on paper: 0.05mg / cm 2 (2Fh image) (The DC voltage of the developer carrier V DC , the charging voltage of the electrostatic latent image carrier V D , and adjusted by laser power) Evaluation image: A 3cm x 15cm image placed in the center of the A4 paper. Fixing test environment: Normal temperature and humidity environment (temperature 23°C / relative humidity 50% (hereinafter N / N)) Fixing temperature: 180℃ Process speed: 348mm / sec

[0157] The above evaluation image was output and the scratch resistance was evaluated. The difference in reflectance was used as an evaluation index for the scratch resistance.

[0158] First, the image portion of the evaluation image is rubbed (10 times back and forth) with a new evaluation paper under a load of 1.0 kgf using a Gakushin type rub fastness tester (AB-301: manufactured by Tester Sangyo Co., Ltd.) After that, the reflectance of the rubbed portion of the new evaluation paper and the reflectance of the non-rubbed portion are measured using a reflectometer (REFLECTOMETER MODEL TC-6DS: manufactured by Tokyo Denshoku Co., Ltd.).

[0159] The difference in reflectance before and after rubbing was calculated using the following formula. The resulting difference in reflectance was evaluated according to the following evaluation criteria. If the evaluation was A to L, it was determined that the effects of the present invention were obtained. Difference in reflectance = reflectance of non-friction area - reflectance of friction area

[0160] (Evaluation Criteria) AA: Less than 1.0% A: 1.0% or more, less than 5.0% B: 5.0% or more, less than 10.0% C: 10.0% or more, less than 15.0% D: 15.0% or more

[0161] [Examples 2 to 32 and Comparative Examples 1 to 7] Evaluation was performed in the same manner as in Example 1, except that two-component developers 1 and 3 to 39 were used instead of two-component developer 2. The evaluation results are shown in Table 6.

[0162] [Table 6]

Claims

1. A toner having toner particles containing a binder resin having a first resin and a second resin, and calcium carbonate particles, the first resin is a crystalline resin and the second resin is an amorphous resin; the content of the calcium carbonate particles in the toner particles is 1% by mass or more and 15% by mass or less, the monomer unit constituting the second resin has any one of a nitrile group, a carboxy group, and a hydroxy group, and the total functional group concentration of these groups is 0.8 mmol / g or more and 10.0 mmol / g or less; a matrix domain structure constituted by a matrix containing the first resin and a domain containing the second resin is present in a cross section of the toner particle observed by a transmission electron microscope, a ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle is 35 area % or more and 70 area % or less; The toner is characterized in that the calcium carbonate particles are contained in an area 100 nm inside from the contour of the cross section of the toner particle.

2. 2. The toner according to claim 1, wherein the calcium carbonate particles have a number average particle diameter Da of 100 nm or more and 500 nm or less in a cross section of the toner particle.

3. 3. The toner according to claim 1, wherein the domain has a number average particle diameter Db of 50 nm or more and 500 nm or less in a cross section of the toner particle.

4. 4. The toner according to claim 1, wherein the second resin is a vinyl resin.

5. 5. The toner according to claim 1, wherein a number average particle diameter Da of the calcium carbonate particles and a number average particle diameter Db of the domains satisfy a relationship of 0.25≦Da / Db≦2.00 in a cross section of the toner particle.

6. The toner according to any one of claims 1 to 5, wherein the monomer units constituting the first resin have monomer units having a nitrile group, a carboxy group, and a hydroxy group, and the total functional group concentration of these monomer units is 0.8 mmol / g or more and 10.0 mmol / g or less.

7. The first resin has a monomer unit represented by the following formula (1):

7. The toner according to claim 1, wherein the proportion of the monomer unit is 30.0% by mass or more based on the total mass of all monomer units of the first resin. 【Chemistry 1】 (In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms.

8. 8. The toner according to claim 1, wherein the surface of the calcium carbonate particles is coated with a fatty acid.

9. 9. The toner according to claim 1, wherein the first resin and the second resin have a nitrile group.

10. The toner according to any one of claims 1 to 9, further comprising a hydrocarbon wax.

Citation Information

Patent Citations

  • Toner for electrostatic charge image development

    JP2013200559A

  • Toner

    JP2014142632A

  • Toner for electrostatic charge image development

    JP2015007692A

  • Electrophotographic toner

    JP2016114828A

  • Toner

    JP2020144321A